PENOKOHAN DALAM NOVEL HABIBIE DAN AINUN KARYA BAHARUDDIN JUSUF HABIBIE (KAJIAN PSIKOLOGI SASTRA) - Purwanto Purwanto (LPPM UNISDA, 2017)
The purpose of this study was to describe (1) the character of Habibie, (2) the character of Ainun, and (3) view of life Habibiein the Habibie and AinunworkedBaharuddinJusufHabibie. Based on data analysis and discussion undertaken in the novel Ainun Habibie and this can be concluded that: a live view of the behavior BJ Habibie culture, religion, and science and technology (science and technology). Everything should be formed in a positive synergy, because these three things is what will determine everything. Cultural behavior must be owned entrepreneurs because they reflect as a nation of Indonesia. Whatever the achievements, even abroad, an entrepreneur will bring a sense of nationalism is high, so a love of culture is never forgotten. Religious behavior is also an important thing as something that will lead to step into direction remains positive.